PEMANFAATAN VIDEO REELS INSTAGRAM SEBAGAI MEDIA PEMBELAJARAN PADA PROGRAM MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) - N. Putri Sumaryani; I Nengah Suka Widana; Ni Wayan Sunita; Luh Gede Ambaradewi (Program Studi Pendidikan Biologi Universitas PGRI Mahadewa Indonesia, 2026)
The Independent Learning and Independent Campus (MBKM) program launched by the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia is a transformative policy in the higher education system. MBKM provides students with the freedom to study outside their study program and even outside the campus, with the primary goal of increasing the relevance of higher education to the world of work. One of the activities that is an integral part of MBKM is the Independent Internship Program. The Independent Internship Program provides students with the opportunity to engage directly in the world of industry, organizations, or other institutions, to gain practical skills not always available in the classroom. The implementation of the internship program applies several theories from integrated courses in the field. As a form of conveying the learning outcomes obtained during the internship, it is realized through the creation of instagram video reels that serve as learning media for conveying activities and also the applied material.